MEMBANGUN PENDIDIKAN POLITIK DALAM FATSUN DEMOKRASI PANCASILA DAN DELIBERATIVE - Nadir, Nadir; Wardani, Win Yuli (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2019)
This paper a study political education to meet presidential elections and vice president of the republic of Indonesia of 2019 in fatsun democracy Pancasila and a deliberative.The results show that in fatsun democracy Pancasila and a deliberative, found the practical discursus, formation public opinion and political aspirations the community, and sovereignty the populace as procedural as the owner of and holder sovereignty highest dealt with in constitutional in Indonesia and can control government decisions that was formed through elections.Political education is a means of to understand rights and obligations and the responsibilities of a citizen in our nation and state, besides the responsibility of presidents and vice president of the republic of Indonesia was elected to carry power as the mandate. The responsibility of in education politics it is it is an obligation of a political party, KPU-Bawaslu, and all elements of the community with the aim of an increase in the understanding of the related the vision mission presidential candidates and a vice president been attained by Indonesia in discursus the public which had bought in accordance with idee and aim of the Indonesia state that is to date it has not yet been attained.